The Four Basic Pillars of Hajj's Mobile System - Makhzoom, Sakina M. A (2011)
The first goal of this research is involve to design and develop a mobile application making the performing of Hajj easy and without any mistake. This quantitative study was adopted in this study. The User awareness on the ease of use and the usability of FBPHMS prototype was estimated using a testing session followed by a questionnaire. It was conducted on 40 respondents. The analysis of the results indicated that the usability of the system was very high on both aspects namely, usefulness and ease of use.